Electrical Stimulation Counteracts Muscle Decline in Seniors - Kern, Helmut; Barberi, Laura; Löfler, Stefan; Sbardella, Simona; Burggraf, Samantha; Fruhmann, Hannah; Carraro, Ugo; Mosole, Simone; Sarabon, Nejc; Vogelauer, Michael; Mayr, Winfried; Krenn, Matthias; et al. (Frontiers in Aging Neuroscience, 2014)
The loss in muscle mass coupled with a decrease in specific force and shift in fiber composition are all marks of aging. Training and regular exercise attenuate the signs of sarcopenia. However, pathologic conditions limit the ability to perform physical exercise. We addressed whether electrical stimulation (ES) is an alternative intervention to improve muscle recovery and defined the molecular mechanism associated with improvement in muscle structure and function. We analyzed, at functional, structural, and molecular level, the effects of ES training on healthy seniors with normal life style, without routine sport activity. ES was able to improve muscle torque and functional performances of seniors and increased the size of fast muscle fibers. At molecular level, ES induced up-regulation of IGF-1 and modulation of MuRF1, a muscle-specific atrophy-related gene. ES also induced up-regulation of relevant markers of differentiating satellite cells and of extracellular matrix remodeling, which might guarantee shape and mechanical forces of trained skeletal muscle as well as maintenance of satellite cell function, reducing fibrosis. Our data provide evidence that ES is a safe method to counteract muscle decline associated with aging.